The geochemical evolution of three alkaline complexes in the Kuboos-Bremen igneous province, southern Namibia - Smithies, Robert Hugh (Rhodes University, Faculty of Science, Department of Geology, 1992)
The Kuboos-Bremen Igneous Province comprises a linear zone of alkaline complexes that intrude Proterozoic and Pan-African rocks and trends in a northeast direction from the northwest of the Cape Province in South Africa into southern Namibia. Of the three most southerly complexes in Namibia. two comprise silicate rocks ranging from nepheline syenite to alkali-granite and are called the Grootpenseiland and Marinkas Kwela Complexes (GPC and MKC). The Marinkas Kwela Carbonatite Complex is the third and most northerly of the complexes. Isotopic age determinations on a number of rock types from both the silicate complexes yield ages around 520Ma and are consistent with published Pan-African ages for the Province. Each silicate complex shows a migrating locus of intrusion from Siundersaturated rocks in the southwest to Si-oversaturated rocks in the northeast. The complexes overlap in outcrop. The rocks are moderately to highly felsiC and none reflects primary magma compositions. The Si-undersaturated rocks from both complexes include side-wall cumulates formed from magmas that fractionated alkali-feldspar, clinopyroxene and amphibole. Foyaites also occur in the MKC and have a compositional range reflecting alkali-feldspar fractionation and, probably, some interaction with dolomite country rocks. Major and trace element data suggest that critically saturated alkali syenites occurring in both complexes evolved via protracted feldspar fractionation, and that critically saturated alkali-feldspar syenite occurring only in the GPC is a cumulate. The two rock types cannot be related genetically. Of the SI-oversaturated rocks in both complexes, those in the compositional range monzonite to granite were intruded before alkali-granites. Compositional diversity amongst the former reflects fractionation of feldspar and of mafic phases, but that process cannot genetically link the rocks to the alkali-granites. Isotopic compositions of Sr and Nd indicate that the silicate magmas were derived from an upper mantle source region characterised by low time-integrated Rb/Sr ratios and high time-Integrated Sm/Nd ratios, However, the evidence of Sr and 0 isotopic data is that the Si-oversaturated melts possibly interacted with a crustal component. presumably the Proterowlc rocks of the Namaqua Metamorphic Province. This interaction may explain the occurrence of apparently co-genetic rock series that evolved on opposite sides of the feldspar join in Petrogeny's Residua System. The Marinkas Kwela Carbonatite Complex was emplaced before the final intrusive phases of the MKC and exhibits unusually pronounced late-stage enrichment in manganese. The earliest intrusive rocks in the complex were nepheline syenites which were fenitised by later intrusions of soÌ‚vites. Although the commonly occurring magmatic sequence of soÌ‚vite-beforsite-ferrocarbonatite is observed at Marinkas Kwela, soÌ‚vites do not appear to have been parental to beforsites. Removal of apatite and early crystallisation of magnetite distinguish magnetite-rich beforsite from co-genetic apatite-rich beforsite. Two further magmatic sequences. the first from apatite-rich beforsite through ferrocarbonatite to Mn-rich ferrocarbonatite (high Fe/Mn) and the second from magnetite-rich beforsite to Mn-rich ferrocarbonatite (low Fe/Mn). reflect fractionation of dolomite and of dolomite+magnetite respectively.
Keywords: Alkalic igneous rocks -- Namibia; Geochemistry -- Namibia